Do Logistics Development and Tourism Development Contribute to Low-Carbon Economy? Empirical Evidence from Technological Innovation and Clean Energy Utilization in China - Guo, Jianquan; Zhang, Yinan (International Journal of Management Innovation Systems, 2024)
With the intensification of the conflict between environmental deterioration and economic growth, low-carbon economy has attracted more and more attention from various industries. Using panel data of 30 provinces in China from 2000 to 2019, this paper adopts a fixed effect model and threshold effect model to study the non-linear threshold effects of logistics development and tourism development on low-carbon economy from the perspective of technological innovation and clean energy. The results show that, firstly, logistics development and tourism development have promoting effects on low-carbon economy; secondly, with the improvement of technological innovation and the increase in the use of clean energy, the promotion of logistics development and tourism development on low-carbon economy are gradually enhanced; finally, there is an obvious regional heterogeneity in the above threshold effects: Within the threshold range, the development of logistics and tourism in the eastern regions has a stronger promoting effect on the low-carbon economy than in the central and western regions.